2009
DOI: 10.2166/aqua.2009.004
|View full text |Cite
|
Sign up to set email alerts
|

Bioleaching of arsenic in a drinking water treatment process

Abstract: Arsenic is found to exist within the shailow zones of groundwater in many countries and a iarge number of drinking water treatment units have been instaiied to combat this arsenic poisoning.Microbial activity can greatly affect the mobiiization of arsenic under anaerobic conditions when coupied with the oxidation of organic matter, in this study, the bioleaching of arsenic in response to organic matter inclusion in a drinicing water treatment process has been elucidated.The decomposition of organic matter due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The observation has been linked with changing of the solid phase to the dissolved phase of arsenic. Previous report (Hasan et al 2009) described mechanism of bioleaching associated with sand filter bed that creates a biofilm in pore space and top of the surface of the bed creating an anaerobic condition that facilitates the bioleaching of arsenic in the outlet water. This mechanism may probably be responsible for the increment in D-As obtained in this study.…”
Section: Removal Of Arsenic In Airpmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation has been linked with changing of the solid phase to the dissolved phase of arsenic. Previous report (Hasan et al 2009) described mechanism of bioleaching associated with sand filter bed that creates a biofilm in pore space and top of the surface of the bed creating an anaerobic condition that facilitates the bioleaching of arsenic in the outlet water. This mechanism may probably be responsible for the increment in D-As obtained in this study.…”
Section: Removal Of Arsenic In Airpmentioning
confidence: 99%
“…Thus, MAIRP is not sufficient for arsenic removal. Meanwhile, increment in concentration may be induced by the sediments in the sedimentation pond as described by Hasan et al (2009). It is therefore suggested that periodic removal of sediment will help to avoid the leaching of arsenic.…”
Section: Removal Of Arsenic In Airpmentioning
confidence: 99%